Components of the formation of the tourist and local lore competence of future geography teachers - Yerlan; Мазбаев, О.; Лайсханов, Ш. (Pedagogy and Psychology, 2022)
In this article, the theoretical foundations and components of preparing geographer students for tourist and local lore work on the basis of a competency-based approach were considered. The importance of improving motivational, active-cognitive and research competencies in the training of future geography teachers was determined. According to an analytical review of research on the organization of professional training of geography teachers, it was discussed that students are geographers who carry out tourist and local lore work. Motivational and emotional-value; active-cognitive and subject; the importance of the components of obtaining new professional knowledge, as well as the competence of self-development and research in the formation of tourist and local lore competencies of geographer students, was determined. A model of the formation of tourist and local lore competencies of geographer students using the methods of theoretical analysis, concretization and generalization has been developed. It was also explained that the defining values for the future geography teacher are knowledge, reliability, fairness, self-esteem, tolerance, creativity and interest in work-professional experience. These values are necessary for future geography teachers to conduct tourist and local lore work. Therefore, we, as geographers, developed the ability to think independently, supported special cognitive tasks for comparison, establishing logical connections. In conclusion, we came to the conclusion that geography is one of the main directions of the reform of higher education and the technology of forming tourist and local lore competencies-values and worldview, vision, perception and understanding of the environment, orientation, personal self - improvement, acquisition of knowledge and experience - allows geographer students to conduct tourist and local lore work.